Rhodamine-naphthalimide demonstrated a distinct aggregation-induced emission mechanism: elimination of dark-states via dimer interactions (EDDI). Issue 10 (15th January 2019) - Qi, Qingkai; Huang, Lu; Yang, Runqing; Li, Jin; Qiao, Qinglong; Xu, Bin; Tian, Wenjing; Liu, Xiaogang; Xu, Zhaochao
Abstract : Rhodamine B-naphthalimide (RhB-Naph ) demonstrated a distinct aggregation-induced emission (AIE) mechanism, different from the restriction of intramolecular rotations or vibrations as in traditional AIE molecules. Abstract : Rhodamine B-naphthalimide (RhB-Naph ) demonstrated a distinct aggregation-induced emission (AIE) mechanism, different from the restriction of intramolecular rotations or vibrations as in traditional AIE molecules. The monomers ofRhB-Naph were non-emissive, due to the presence of a dark S1 state. Upon molecular aggregation, intermolecular interactions significantly altered the electronic properties ofRhB-Naph, leading to the formation of a bright S1 state and endowingRhB-Naph with notable AIE properties. Besides, we demonstrated thatRhB-Naph enabled the development of a solid-state three-color fluorescent switch upon multi-external stimuli.